Investigation into UAV Applications for Environmental Ice Detection and De-Icing Technology - Qingying Li; Zhijie Chai; Rao Yao; Tian Bai; Huanyu Zhao (Drones)
In cold environments, ice formation poses significant risks to infrastructure such as transportation systems and power transmission. Yet, traditional de-icing methods are often time-consuming, hazardous, and inefficient. In this regard, unmanned aerial vehicles (UAVs) have shown great potential in environmental ice detection and de-icing applications. This study comprehensively reviews the application of UAVs in ice detection and de-icing operations in external environments, emphasizing their potential to replace traditional manual methods. Firstly, the latest developments in UAV-based external ice detection technology are examined, with a focus on the unique capabilities of sensors such as multispectral cameras, infrared imagers, and LiDAR in capturing specific ice features. Subsequently, the implementation and effectiveness of chemical, mechanical, and thermal de-icing methods delivered via UAV platforms are evaluated, focusing on their operational efficiency and adaptability. In addition, key operational requirements are reviewed, including environmental adaptability, mission planning and execution, and command transmission, as well as system design and manufacturing. Finally, the practical challenges involved in deploying UAVs under complex weather conditions are examined and solutions are proposed. These are aimed at promoting future research and ultimately driving the adoption of UAV technology in de-icing applications.